Researches of characteristics of installation for a circular purge - Зінченко, В.П.; Зінченко, Н.П.; Гуржій, А.М. (Proceedings of National Aviation University (archive), 2012)
Results of experimental researches of characteristics of installation for a circular purge of models of flying devices in wind tunnels in conditions of the big corners of sliding as development of hardware-software complexes which are modern means of reception of the information and knowledge in information technologies of design researches are stated.